2021
DOI: 10.1111/opo.12908
|View full text |Cite
|
Sign up to set email alerts
|

Fluid reservoir thickness and aberration relationship in keratoconic eyes with scleral lenses

Abstract: Purpose To investigate the effect of varying the fluid reservoir (FR) thickness of scleral lenses (SL) on corrected distance visual acuity (CDVA), contrast sensitivity (CS) and higher‐order aberrations (HOAs) in keratoconic eyes. Methods Forty eyes with keratoconus were fitted with a diagnostic Boston Sight SL having three different FR thicknesses. CDVA, CS and HOAs were measured before and after 30 min of lens wear. An i‐Trace aberrometer and anterior segment optical coherence tomography (AS‐OCT) were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…CS has been considered a very sensitive assessment for visual disturbances because of a higher amount of HOAs 28 and the Pelli–Robson CS test as a standard measuring tool to quantify visual performance in keratoconus eyes. 29 The current study reported reduced baseline CS, which was consistent with the previous studies, 20 and showed noticeable improvement with all three lenses with different eccentricities in keratoconus corneas, which were in comparison with the previous studies. 17,18 Present studies have reported better CS with FSE1 and FSE2 when compared with FSE0 but were not clinically or statistically significant and showed a difference of only two or 3 letters in the Pelli–Robson chart.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…CS has been considered a very sensitive assessment for visual disturbances because of a higher amount of HOAs 28 and the Pelli–Robson CS test as a standard measuring tool to quantify visual performance in keratoconus eyes. 29 The current study reported reduced baseline CS, which was consistent with the previous studies, 20 and showed noticeable improvement with all three lenses with different eccentricities in keratoconus corneas, which were in comparison with the previous studies. 17,18 Present studies have reported better CS with FSE1 and FSE2 when compared with FSE0 but were not clinically or statistically significant and showed a difference of only two or 3 letters in the Pelli–Robson chart.…”
Section: Discussionsupporting
confidence: 92%
“…SL tilt and decentration secondary to improper haptic alignment 9,35 and higher FRT 8 are related to HOAs by inducing a significant amount of aberrations. Contrary to these results, Balakrishnan et al 20 found no significant impact of higher FRT on HOAs. In the current study, all these lenses were trial lenses from the diagnostic set, although the authors did not report any significant amount of tilt or decentration clinically, the measurements over final patient lenses could have yielded a better result by avoiding lens tilt and decentration, which need further analysis.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations